2005
DOI: 10.1002/art.21414
|View full text |Cite
|
Sign up to set email alerts
|

Is antibody clustering predictive of clinical subsets and damage in systemic lupus erythematosus?

Abstract: Objective. To examine autoantibody clusters and their associations with clinical features and organ damage accrual in patients with systemic lupus erythematosus (SLE).Methods. The study group comprised 1,357 consecutive patients with SLE who were recruited to participate in a prospective longitudinal cohort study. In the cohort, 92.6% of the patients were women, the mean ؎ SD age of the patients was 41.3 ؎ 12.7 years, 55.9% were Caucasian, 39.1% were African American, and 5% were Asian. Seven autoantibodies (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
122
4
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(143 citation statements)
references
References 37 publications
(43 reference statements)
13
122
4
1
Order By: Relevance
“…In the second cluster analysis, after inclusion of aPL, we identified 4 separate clusters of autoantibodies (Table 1). Three clusters identified in our analysis were similar to autoantibody profiles previously described in patients with SLE by To and Petri 9 . In our analysis we additionally identified a cluster characterized by the absence of specific autoantibodies.…”
Section: To the Editorsupporting
confidence: 87%
“…In the second cluster analysis, after inclusion of aPL, we identified 4 separate clusters of autoantibodies (Table 1). Three clusters identified in our analysis were similar to autoantibody profiles previously described in patients with SLE by To and Petri 9 . In our analysis we additionally identified a cluster characterized by the absence of specific autoantibodies.…”
Section: To the Editorsupporting
confidence: 87%
“…1,2 Most noteworthy among these disorders are the various forms of primary and secondary nephrotic syndrome, 1,2 systemic lupus erythematosus with "lupus anticoagulant", 3 granulomatous vasculitis (Wegener's granulomatosis), 4 and Behçet syndrome. 5 In the recent past, the greatest attention to thromboembolic risk and its management has been given to the nephrotic syndrome.…”
mentioning
confidence: 99%
“…This activation has been demonstrated by the presence of at least 30 different types of autoantibodies related to APS. 27 The higher frequency of deep venous thrombosis in ANA Hep-2 positive individuals had been demonstrated in patients with SLE; 28,29 however, studies demonstrating these findings in patients with PAPS cannot be found in the literature. It is known that SLE patients are at higher risk to develop thromboembolic phenomena and that this risk is higher when antiphospholipid antibodies are present.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that SLE patients are at higher risk to develop thromboembolic phenomena and that this risk is higher when antiphospholipid antibodies are present. [28][29][30] In addition, there seems to be clusters of autoantibodies, such as a combination of aCL, antinative DNA, and LAC, that discriminate a population of SLE patients with a higher risk of thromboembolic events. [28][29][30] The present study demonstrated that approximately 1/3 of PAPS patients could be ANA Hep-2 positive and most of these individuals had titers > 1/320.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation